Multiple biochemical responses, osmoregulation, fatty acid composition, and vitamin E level in crayfish as biomarkers of exposure to thiacloprid and trifloxystrobin pesticides - Uckun, Mirac; Uckun, Aysel Alkan; Oz, Ozden Barim; Yologlu, Ertan (Elsevier, 2025)
Neonicotinoids and strobilurins are commonly used pesticides in agriculture, posing significant risks to aquatic animals. In this study, the toxic effects of thiacloprid and trifloxystrobin on Astacus leptodactylus were evaluated using various biomarkers, including acetylcholinesterase, carboxylesterase, glutathione S-transferase, glutathione reductase, alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase, total antioxidant content, total oxidant scavenging capacity, adenosine 5'-TriPhospahatases, fatty acid composition, and vitamin E level. Both pesticides significantly affected the biomarkers compared to the control, activating and inhibiting them. Exposure to the pesticides led to an increase in monounsaturated and saturated fatty acids and a significant decrease in polyunsaturated fatty acids and vitamin E. The study's findings suggest that thiacloprid and trifloxystrobin have harmful effects on A. leptodactylus through oxidative stress, detoxification, cholinergic, osmoregulation, and food quality systems. It is possible to conclude that these pesticides pose a major risk to public health as well as the aquatic ecology.
Keywords: Aquatic invertebrates; Fatty acid composition; Oxidative stress biomarkers; Pesticide toxicity; Vitamin E